A novel non-invasive electrical synchrony method to improve cardiac resynchronization therapy responders. (25th November 2020) - Logarzo, E; Ortega, D; Barja, L; Paolucci, A; Mangani, N; Revollo, G; Aboy, J
Abstract: Introduction: Cardiac resynchronization therapy (CRT) has emerged as an important treatment for patients with heart failure and reduced ejection fraction (EF) despite optimal pharmacological therapy. Some studies showed non-responders rate near 30%. Nowaday there is no gold standard method for selection, evaluation and follow up on this group of patients. Multiple techniques used and operator dependence made echocardiogram failed. Synchromax 2 is a device designed to evaluate non-invasive electrical synchrony. It is fast, reproducible and non-operator dependent. Synchromax was evaluated and correlated with other techniques in previous studies. Objective: Evaluate CRT response rate guided by electrical synchrony during the device implantation and follow up. Material and methods: 43 patients were evaluated in an institution in Buenos Aires. A ICD-CRT was implanted in all patients due dilated cardiomyopathy, low EF (less than 35%) and left bundle branch block (LBBB). Non-invasive electrical synchrony evaluation (Synchromax 2) was performed in all patients in baseline condition, during device implantation and the follow up. Synchrony index and curves were analyzed. Curve type 4 and index between 0, 4 and 0, 7 were considered synchronous. Curve type 6 and 10 and index more than 0.7 were considered disynchronous. Interventricular intervals were modified to achieve the best curve and synchrony index. Super responders were considered when EF increased >50%. Baseline and 6 month after implantation echocardiogram were performed. Results: Mean age 64 years. 39% females. Non-coronary dilated cardiomyopathy was main aetiology (63, 1%). EF baseline average was 27%. A baseline index more than 0, 7 was in 73, 3% of the patients. Curve 6 was the most frequent (55, 2%). Follow up average EF was 39% (increased 12%), the super responders rate was 18, 6% (8 patients). Type 4 curve and index between 0, 4 and 0, 7 were achieved in 28 cases (65, 1%). EF increased from 23% (baseline) to 42% (follow up). Average 19%. Type 4 curve was not achieved in 15 patients (34, 9%). In this group, EF increased from 29% (baseline) to 34% (follow up). Average 5%. Conclusion: Electrical synchrony evaluation using Synchromax 2 during ICD-CRT device implantation improves responders rate. When synchronous type 4 curve is achieved EF improves significantly. If type 4 curve is not found results will be unsuccessfully. Synchromax is fast, simple and non-operator dependent. Funding Acknowledgement: Type of funding source: None